Relationship Between Duration of Gadget Use and Insomnia Incidence in Adolescents at Junior High School Betzata ABD Leilem - Eireine Maria Pandoh (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Many teenagers now spend most of their time playing gadgets. The teenagers can spend all day playing gadgets. The teenagers can spend all day playing gadgets. Using for a long time causes them to take about 60 minutes longer to fall asleep than usual, resulting in them experiencing insomnia. The purpose of this study is to determine the relationship between the duration of gadget use and the incidence of insomnia in adolescents at Betzata ABD Leilem Junior High School. Sampling in this study with the Slovin formula, as many as 62 respondents. Data collection using questionnaires via google forms. The data analysis in this study was univariate and bivariate analysis (Chi square test) measuring the relationship between each variable with a valeα= 0.05. The results of the study were obtained, there was a relationship between the duration of gadget use and the incidence of insomnia with a value = 0.06 (value < 0.05). The conclusion in this study is that there is a relationship between the duration of gadget use and the incidence of insomnia in adolescents at Betzata ABD Leilem Junior High School.